Regulation of soil CO2 and N2O emissions by cover crops: A meta-analysis - Muhammad, Ihsan; Sainju, Upendra M.; Zhao, Fazhu; Khan, Ahmad; Ghimire, Rajan; Fu, Xin; Wang, Jun (Soil & tillage research, 2019)
•Soil CO2 emissions increased and N2O emissions varied with cover crop species.•Increased cover crop biomass increased CO2 emissions, but decreased N2O emissions.•Both CO2 and N2O emissions decreased polynomially with increased cover crop biomass C/N ratio.•Responses of CO2 and N2O emissions to cover crop varied with management practices and soil texture. Cover crops provide multiple agronomic and environmental benefits, such as enhanced soil carbon sequestration, aggregation, water infiltration, and reduced erosion and nutrient leaching compared with no cover crop. However, little is known regarding the effect of cover crop species, biomass quality and quantity, and method of residue placement on greenhouse gas (GHG) emissions. Using meta-analysis, this study examined the effect of cover crop species, quality and quantity of biomass, and residue management on response ratios (RRs) of cover crops to no cover crop on CO2 and N2O emissions following cash crops. All cover crop species increased CO2 emissions, but reduced N2O emissions compared with no cover crop, except legumes which increased N2O emissions. Cover crop biomass explained 63% of variability in increased CO2 emissions and 55% of variability in decreased N2O emissions. Both CO2 and N2O emissions decreased polynomially with increased cover crop biomass C/N ratio, with greater rate of decline for legumes than nonlegumes. Cover crop residue incorporated into the soil increased CO2 and N2O emissions compared with the residue placed at surface or removed from the soil. Cover crops emitted lower CO2 and N2O emissions than no cover crops in silty loam and sandy clay loam soils, respectively, compared to clay loam and silty clay loam soils. Both soil organic carbon and total nitrogen increased with cover crop compared to no cover crop. Although CO2 and N2O emissions varied with cover crop species, using legume and nonlegume cover crop mixture to enhance residue C/N ratio compared to legumes and placing the residue at the surface instead of incorporating into the soil can reduce GHG emissions. Because of enhanced soil C and N storage and other known benefits, improvement in soil health and environmental quality due to cover crop may outweigh CO2 emissions compared to no cover crop.